Strategi Layanan Edukatif bagi Anak di Panti Asuhan - Ismaniar, Ismaniar (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2018)
The orphanage is a social institution that provides services for children with non-intact family backgrounds or disadvantaged families from the economic side. The existence of the Orphanage plays a strategic role in the development of each foster child, because the institution serves as a family substitute. To be able to perform the function then the orphanage manager must understand and understand the various functions of the family that must be replaced. In order for the service process can be done well then the caregiver needs to master a variety of strategies suitable for children. The educative service strategy discusses the various steps or ways that orphanage managers can perform to provide optimal services for children in orphanages.